Characterization and correlation of engineering properties with microstructure in peanuts: A microscopic to macroscopic analysis - Fei Xiang; Zhenyuan Li; Yichen Zheng; Caixia Ding; Benu Adhikari; Xiaojie Ma; Xuebing Xu; Jinjin Zhu; Bello Zaki Abubakar; Aimin Shi; Hui Hu; Qiang Wang (Journal of Integrative Agriculture)
Peanut varieties are diverse globally, with their characters and nutrition determining the product quality. However, the comparative analysis and statistical analysis of key quality indicators for peanut kernels across the world remains relatively limited, impeding the comprehensive evaluation of peanut quality and hindering the industry development on a global scale. This study aimed to compare and analyze the apparent morphology, microstructure, single-cell structure, engineering and mechanical properties, as well as major nutrient contents of peanut kernels from 10 different cultivars representing major peanut-producing countries. The surface and cross-section microstructure of the peanut kernels exhibited a dense “blocky” appearance with a distinct cellular structure. The lipid droplets were predominantly spherical with a regular distribution within the cells. The single-cell structure of the kernels from these 10 peanut cultivars demonstrated varying morphologies and dimensions, which exhibited correlations with their mechanical and engineering properties. Furthermore, the mass loss versus temperature profiles of the peanut kernels revealed five distinct stages, corresponding to moisture loss, volatile loss, protein denaturation, and the degradation of various biomacromolecules. Variations were also observed in the lipid, protein, and sucrose contents, texture, bulk density, true density, porosity, geometric mean diameter, and sphericity among the different peanut varieties. This study establishes relationships and correlations among microstructure, engineering properties, and nutritional composition of commonly grown peanut varieties in major peanut-processing countries. The findings provide valuable insights into peanut quality evaluation, empowering the peanut industry to enhance their processing and product development efforts.